Tuberculosis of bilateral sacroiliac joints with bilateral psoas abscess: an unusual presentation - Sandanshiv, Sumedh; Mishra, Anand; Singh, Mohit; Varshney, Anurag (International Journal of Research in Orthopaedics, 2023)
Infectious diseases usually affect the sacroiliac joint unilaterally. Out of all tuberculosis cases, bone tuberculosis is reported in 3-5% of cases. The purpose of this case report is to draw attention to the diagnostic challenge of bilateral tuberculous sacroiliitis with psoas abscess, as this clinical picture is very rare. Tuberculosis of the sacroiliac joint is often missed due to vague symptoms. More often, patients are examined in the supine position, thereby overlooking the sacroiliac joint. Involvement of the sacroiliac joint is rare, but exact numbers are not available. Our case report shows a complication of skeletal Tb that a psoas abscess may develop, causing nonspecific symptoms.